(untitled) (World Science, 2019)
Numerous dental manipulations are accompanied by bone injuries. Various types of drug correction are widely used for correction and optimization of bone tissue reconstruction after bone-traumatic injury. The evaluation of the course of reparative osteogenesis becomes possible with the x-ray methods which gives the possibility to evaluate and predict early quantitative and qualitative changes in various pathological conditions, as well as to trace their dynamics in clinical and experimental conditions. In our research we have find out the peculiarities of the density dynamics of the bone tissue of the mandible after causing bone-traumatic injury to intact animals and animals that have been taking nalbuphine for a long time, as well as after treatment with lincomycin.